2006
DOI: 10.1136/jcp.2005.031807
|View full text |Cite
|
Sign up to set email alerts
|

Primary effusion lymphoma with skin involvement

Abstract: Primary effusion lymphoma (PEL) was once defined as a body cavity-based lymphoma without identifiable contiguous tumour mass, but is now recognised as an independent clinicopathological entity. The case of a 67-year-old Japanese woman with PEL is reported, in which the clinical findings showed a pericardial effusion and multiple erythema on the hypogastrium and inguinal region. The histopathological findings showed a diffuse infiltration of large neoplastic B cells from the dermis to the subcutis. After the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…The mean survival time of PEL is approximately 4-6 months; however, in the review of Adiguzel et al [4] of 31 cases of HHV-8-negative effusion lymphoma, the mean survival time was 10.1 months and the mean follow-up period of 13 living patients was 19.5 months [4]. In our two cases, the tumor regressed without any treatment other than drainage of the effusion, and 7 cases of HHV-8-negative effusion lymphoma presenting a similar phenomenon have been reported in the literature [4,5,6,7,8,10]. In 5 cases (including our 2 cases) of these 9 cases, lymphoma cells were involved in the pericardial effusion.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The mean survival time of PEL is approximately 4-6 months; however, in the review of Adiguzel et al [4] of 31 cases of HHV-8-negative effusion lymphoma, the mean survival time was 10.1 months and the mean follow-up period of 13 living patients was 19.5 months [4]. In our two cases, the tumor regressed without any treatment other than drainage of the effusion, and 7 cases of HHV-8-negative effusion lymphoma presenting a similar phenomenon have been reported in the literature [4,5,6,7,8,10]. In 5 cases (including our 2 cases) of these 9 cases, lymphoma cells were involved in the pericardial effusion.…”
Section: Discussionsupporting
confidence: 59%
“…Eight cases did not experience a relapse (follow-up period 7-25 months, median 16 months). In one case, the tumor relapsed in the skin, and the patient died from a cause other than the tumor [10]. Two cases were associated with HCV infection (chronic hepatitis and cirrhosis) and EBV was not detected in any case.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that HHV-8-negative PEL highly expresses B-cell markers, called PEL-like lymphoma [4]. It has also been reported that the malignant cells of HHV-8-unrelated HIV-negative PEL-like lymphoma patients disappear spontaneously without chemotherapy after serous effusion aspiration or drainage [3,[5][6][7][8]. We report two cases of HHV-8-unrelated HIV-negative PEL-like lymphoma in whom no malignant cells were present after effusion drainage alone.…”
Section: Introductionmentioning
confidence: 99%
“…10 The lymphoid neoplasms that are being diagnosed in fluid cytology are ALL, 1 hairy cell leukemia, 19 chronic lymphocytic leukemia, 17 Burkitt's lymphoma 18 and PELs. 14 Morphology of rare cases of T-cell ALL in serous body fluids has been described in which the neoplastic cells have displayed "ameboid movement" or "hand mirror configuration." This configuration has been attributed to motility and immunologic processes.…”
Section: Discussionmentioning
confidence: 99%
“…These include ALL 1,2,12 ; acute myeloblastic leukemia 6,7,12 ; chronic myelogenous leukemia in the chronic phase 13 as well as blast crisis 1 ; lymphomas, including rare cases of primary effusion lymphoma (PEL) 14 ; and Hodgkin's disease. 12 A pericardial effusion may occur as an initial manifestation 2 or as a complication during the course of the disease.…”
Section: Discussionmentioning
confidence: 99%